The Parijata Tree - And Other Tales of Krishna - Anant Pai; Amar Chitra Katha Pvt Ltd (Mumbai Amar Chitra Katha, 2011)
When Satyabhama, Krishna's fiery wife, gets offended by the behaviour of Indra's wife Shachi, the two gods come to war over the lovely Parijata Tree. The Princess Lakshmana is determined to marry Krishna. Her father must ensure that during the swayamvara only Krishna will win his daughter. Sage Narada Provokes Satyabhama into agreeing him to give Krishna, unless she can find something heavier than him. But all her possesions together prove to be lighter than Krishna
Keywords: Amar Chitra Katha -- Amar Chitra Katha